Predictors of Voluntary HIV Counselling and Testing Services Utilization Among People with Disabilities in Addis Ababa, Ethiopia - Aderemi, Toyin Janet; Mac-Seing, Muriel; Woreta, Seblewangel Ayalew; Mati, Komi Agbemavi (Taylor and Francis, 2014)
The study investigated HIV testing prevalence and factors associated with the utilization of voluntary HIV counseling and testing (VCT) services among individuals with disabilities in Addis Ababa. The analysis was based on a survey of 209 men and 203 women with disabilities, aged 15–49, who had ever heard about HIV and AIDS in four sub-cities in Addis Ababa. HIV testing prevalence was 53.2%, with no significant difference between males and females. Comprehensive HIV knowledge, living with spouse, and religious affiliations positively predicted utilization of VCT services among participants. Living with both parents and having physical or mental/intellectual disabilities were negative predictors of VCT services utilization. More research on the predictors of utilization of VCT services by gender and urban/rural divides are needed among people with disabilities.